A Textbook of Electrical Technology: Vol. 2,. AC and DC machines - Theraja, B. L.; Theraja, A. K. ([VOL.11l.] : S Chand & Co Ltd, 2016)
International edition.
Keywords: Electricity; Electrical engineering; Electric currents, Direct